The Quo Vadis Weaknesses in the Corruption Law Enforcement - Ayu, Hanuring; Dwi, Itok; Harjono, Harjono (Law Development Journal, 2023)
The purpose of this study is to determine the Law Enforcement Arrangements for Corruption in Positive Law in Indonesia, and analyze the weaknesses of law enforcement of corruption in Indonesia. The method of approach used in this research is normative legal research. The results of this study are the weaknesses of law enforcement in Indonesia, including the weaknesses of legal substance, namely the existence of the principle of differentiation in the Criminal Procedure Code, many articles are multi-interpreted so that legal certainty is not guaranteed. The weakness of legal structure is the overlapping authority between law enforcement agencies in investigating corruption crimes. The weakness of legal culture is the existence of a legal culture of compromise, peace, patrimonial values and the attitude of the people who consider corruption cases as a breeze and ignorance of the law enforcement procession.